(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Adolescence is the most crucial developmental stage of an individual life as the learner passes through physiological, biological and emotional transitions that demand adjustment in various situations. School environment plays an instrumental role in social development and adjustment of an adolescent. Different types of schools may have a differential effect on adjustment level of adolescents. The present study is an attempt to study levels of adjustment of female adolescents in co-education and non co- education schools. The study conducted on 200 female adolescents, 100 each from co- education and non co-education schools selected randomly from schools of Punjab found that female adolescents studying in non co- educational schools have better levels of adjustment. The findings have important implications for educationists that attention needs to be paid towards developing strategies for improving adjustment levels of female adolescents for a better society.